Teori semiotik: tanda bahasa dan wacana sastera (Jurnal Bahasa, 2001)
Semiotics is considereal as an important theory in the discourse of language and literature. The history started from the Ferdinand de Saussure's thinking and later the idea was further developed by Charles Sanders Peirce .in understanding language and literature texts. The fundamenta!s of semiotic comprise the following aspects - signified. The interpretation and cognition of semiotics in the modem era tend to direct towards a search for a certain meaning or definition. The quest for the meaning has brought changes during the postmodern era by stating that a partcular sign has multiple meaning or plural in nature and inconsistent. In the world full with the contemporary signs, semiotics as a method of interpreting 'meaning is very functional the discourse of language and literature.